Does The Indonesian National Standard (SNI) for Products in SMES Influence Cleaner Production Practices? A Snapshot of Best Practices from Yogyakarta, Indonesia - Muhammad Imron Rosyidi; Maria Theresia Sri Budiastuti; Mugi Rahardjo; Totok Gunawan (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
This article investigates the extent to which the Indonesian National Standard (SNI) for products adopted and applied by small and medium enterprises (SMEs) in Yogyakarta, Indonesia, can encourage them to effectively implement a quality management system (QMS) within their internal organizations, which eventually affects and benefits their process performance and clean production practices. Survey data collected from 44 respondents in 12 SMEs with SNI-certified products were processed and examined using descriptive analysis and regression analysis. The results showed that these could implement QMS effectively partly because it is a requirement for the SNI certification of the proposed product. The effectiveness of QMS implementation affects the achievement of process performance in that it can reduce the number of defective products, process costs, and process cycle times. According to the respondents, an effective QMS makes every activity and action taken in the production process more environmentally friendly and leads to cleaner production practices. These findings can help further research determine the model's feasibility to design and develop a better framework that promotes QMS and clean production practices, especially among SMEs in Indonesia.